Kebijakan Pendidikan dalam Menyiapkan Sumber Daya Manusia (SDM) yang Berkualitas - Munardji Munardji (Tarbiyah Departement collaboration with AMCA, 2013)
Current world constantly growing tendency that affects many joints of human life. It changes so fast and sometimes unpredictable. Therefore, in order to follow the changes that can be retrieved anticipation for human welfare. From an educational perspective, it can only be done and prepare qualified human resources.